Keputusan Pembelian Produk Skincare: Pengaruh Brand Image, Labelisasi Halal, dan Electronic Word Of Mouth - MH Ainulyaqin; Adrianna SR; Listian I. Achmad; Sukron Mamun; Fatmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aimed to determide how much brand image, halal labeling, and electronic word of mouth influenced purchasing decisions. The research method used in this research is quantitative with a descriptive approach. The data used in this study obtained by distributing questionnaires to 100 MS Glow skincare comsumers located in Karawang Regency. The data was processed using SmartPLS 4.0 application. The results of this study indicated that brand image had a positive influence significantly to purchasing decisions, the halal labeling has a positive and significant influence on purchasing decisions, and electronic word of mouth have an influence on purchasing decision.